ANALISIS PEMOSISIAN SISWA PADA AKTIVITAS DISKUSI DENGAN BERBANTUAN PERUBAHAN KELOMPOK DI SEKOLAH DASAR - Nury Azkiya Umamy; Sudirman Sudirman; Subanji Subanji (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
Student positioning in discussion activities with group change patterns can be used to determine student positions when interacting with group members. Group changes are useful for deciding student positions in three meetings held. The purpose of this study was to describe how student positioning occurs in discussion activities with group change patterns. The research method used is descriptive qualitative research with a phenomenological type. The research instruments were group worksheets, student observation sheets, and documentation in pictures and recordings. Data analysis in this study was data reduction, data presentation, and conclusion. The results showed that with student positioning, students could determine their positions during interactions in discussion activities. The interaction resulted in group changes used to determine the differences in the positions of the four students at each meeting, as well as the consistency of student positioning to determine the extent to which the four students were consistent in providing ideas or suggestions.